2017
DOI: 10.18520/cs/v112/i03/619-624
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effects of Fluorine Substitute 3,5-di-<i>tert</i>-butylphenol Bearing Schiff Bases Using CFSE-Based Cell Proliferation Assay

Abstract: The determination of antiproliferative properties of compounds on tumour cells is important for assessment of their efficacy in cancer treatment. CFSElabelled K562 cells were incubated with doxorubicin and ortho-or para-fluorosubstitute Schiff bases (compounds 1 and 2 respectively). CFSE intensities were analysed using flow cytometry. K562 cells treated with doxorubicin resulted in homogeneous high intensity fluorescence after 96 h of incubation. Schiff bases exhibited antiproliferative effects, but lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a recent study, aminophenylhydrazine SB compounds were tested for their antiproliferative capacity on A549 cells and showed that those containing two fluorine atoms had the strongest antiproliferative effect compared to five fluorine atoms [42]. Another study with SB compounds carrying fluorine atoms in the ortho and para positions showed that the antiproliferative effects of the compounds on K562 cells were lower than that of DOX [43]. In our study, although the lowest PI value among SB ligands was obtained with 5 fluorinated compounds, this antiproliferative capacity lagged behind DOX, which is the standard chemotherapeutic drug.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, aminophenylhydrazine SB compounds were tested for their antiproliferative capacity on A549 cells and showed that those containing two fluorine atoms had the strongest antiproliferative effect compared to five fluorine atoms [42]. Another study with SB compounds carrying fluorine atoms in the ortho and para positions showed that the antiproliferative effects of the compounds on K562 cells were lower than that of DOX [43]. In our study, although the lowest PI value among SB ligands was obtained with 5 fluorinated compounds, this antiproliferative capacity lagged behind DOX, which is the standard chemotherapeutic drug.…”
Section: Discussionmentioning
confidence: 99%